Vietnam : Higher Education and Skills for Growth - World Bank (Washington, DC, 2012)
The demand for skills has been increasing significantly in Vietnam, due to a combination of inter-industry employment changes, capital accumulation and some evidence which is consistent with skill-biased technical change. As a result employment opportunities for tertiary graduates now exist in most sectors. Higher education graduates are also shown to contribute positively to firm productivity. On the one hand, this evidence provides a strong justification for further expansion and improvement of higher education in the country. On the other hand, low research and development (R&D) capacity, increasing evidence of skill bottlenecks and the still inequitable distribution of higher education opportunities, combined with broad institutional and financing constraints, suggest that the higher education system does not yet have the tools it needs to adapt to the growing and changing needs of an increasingly dynamic economy. Moving towards a first-class high performing higher education system will require a set of reforms that create a more flexible and diverse system, with, among other characteristics, more private sector participation and greater emphasis on research with the potential development of centers of excellence. To get there, Vietnam will need to create supporting governance and financing frameworks, with a revised role for the public and private sector. It may consider pursuing a reform agenda in three stages: strengthening the framework for a competitive higher education system, helping universities improve the relevance of decision making for the emerging social and economic needs, and further investments in building a first class higher education system.